Dynamic simulation of a microcogeneration system in a Spanish cold climate. (1st June 2018) - Marrasso, E.; Roselli, C.; Sasso, M.; Picallo-Perez, A.; Sala Lizarraga, J.M.
Highlights: A microcogeneration system is numerically analysed in a load sharing approach. A model is developed to dynamically simulate the system. Dynamic simulation of two residential buildings connected through a micro-grid. Comparison between the performance of proposed and reference systems. Investigation of different economic incentives influencing the microcogeneration. Abstract: Microcogeneration systems guarantee the reduction of primary energy consumption and greenhouse gas emissions in residential sector, by reducing fossil fuels demand and grid losses with respect to conventional energy conversion systems. Energy, environmental and economic benefits can be obtained sharing the cogenerated thermal and electric energy among different end-users to increase the operating hours of the microcogeneration plant with respect to the scenario in which energy demand of each end-user is satisfied by a single cogeneration system. This paper analyses a microcogeneration system used to satisfy electric, space heating and domestic hot water demands of two separate residential buildings located in Spain in a load sharing approach. It consists of a natural gas fuelled internal combustion engine with a thermal and electric power of 12.5 kW and 5.5 kW, respectively. An auxiliary boiler with a nominal thermal power of 24 kW, is also included. The domestic hot water and the heating requirements are managed by means of two different thermal energy storages. The proposed energy conversion systems were experimentally analysed in a test facility in Vitoria Gastéiz (Spain). The models representing the components and the buildings have been implemented in TRNSYS 17. The energy, environmental and economic performance of proposed system are compared with those achieved by a traditional system based on separated energy production. The results highlight that the load sharing between users with different load profiles leads to better environmental and thermo-economic results with respect to the conventional system. The microcogeneration plant works for about 3000 hours per year achieving a primary energy saving of 12.1% and a reduction of equivalent CO2 emissions equal to 27.8%. The payback period of the analysed solution is equal to 11.9 years unless economic support mechanisms are considered. The results of this study show that the introduction of a microcogeneration system in load sharing approach leads to energy, environmental and economic benefits even considering two separate residential buildings, occupied by users with different behaviour.